Optimization of mechanical properties of CNT-rubber nanocomposites. (2021) - Jawahar, P.; Payak, V.; Chandradass, J.; Prabhu, P.
Abstract: Rubber nanocomposites were prepared by adding required amount of Multiwall carbon nanotubes (MWCNT) in varying proportions (0.5, 1, 1.5, 2 and 2.5 wt%) as nano reinforcement and carbon black in varying proportion (0, 10, 20, 30 and 40 phr) as filler. The chemicals were added in the following order (Natural Rubber, Antioxidant: 1 phr, Oil: 5 phr, Zinc Oxide: 4 phr, Stearic Acid: 2 phr, Accelerator: 1 phr, Sulfur: 2phr) in double roll mill to process rubber nanocomposites. The result revealed that the incorporation of Multiwall carbon nanotube (MWCNT) has significantly improved the mechanical properties of natural rubber. In this work an attempt has been used to find rubber nanocomposite system which posses best combined mechanical by TOPSIS Method.